The effect of financial technology (FinTech) adoption on individual over-indebtedness in asean-5 countries/ Ahmad Fauze Abdul Hamit, Ninalyn Fridrict and Maryam Qaameelah Othman - Abdul Hamit, Ahmad Fauze; Fridrict, Ninalyn; Othman, Maryam Qaameelah (Universiti Teknologi MARA, Sabah, 2024)
This article examines the impact of financial technology (FinTech) on individual over-indebtedness in ASEAN-5 countries (Malaysia, Indonesia, Thailand, Singapore, and the Philippines). While FinTech has revolutionised financial services, enhancing accessibility and efficiency, it raises concerns about overindebtedness, where individuals struggle to meet debt obligations. The study investigates how FinTech, alongside macroeconomic factors such as household consumption, economic growth, unemployment, and inflation, influences overindebtedness. Utilising a static quantitative panel data approach from 2010 to 2020, the research finds that FinTech Adoptions negatively correlate with over-indebtedness, suggesting that FinTech can enhance financial stability through improved financial literacy alongside the financial credit assessment capabilities. Conversely, higher household consumption is positively associated with over-indebtedness, indicating that increased borrowing to finance consumption leads to higher debt levels. Economic growth shows a negative relationship with overindebtedness, as improved economic conditions enhance individuals' ability to repay debts. Unemployment rates also negatively correlate with over-indebtedness, highlighting the complex interplay between employment and borrowing behaviours. Inflation, however, is statistically insignificant in affecting over-indebtedness. Nonetheless, the study's limitations include potentially overlooking the dynamic cultural differences within the ASEAN-5 countries, and the complex interplay between the economic conditions and impulsive borrowing behaviors of these countries. Finally, this research contributes to understanding the multifaceted nature of over-indebtedness and the role of FinTech in shaping financial behaviours in ASEAN-5 countries that could provide relevant insights to individuals, academics and policymakers for further development.